Պաշտպանության բանակի ինժեներական ծառայության 2005-2008 թթ. գործունեությունից - Հարությունյան, Մ. Ա (ԱրՊՀ հրատ․)
In 2005-2008 the main efforts of Defense Army engineering service were directed towards the support of the stuff security included in military duty, the improvement of engineering constructions and barriers, fulfillment of the given tasks and planned engineering activity. The tasks set were arisen to enhance degree of enemy’s fire wounding and from the necessity of keeping the first line defense system permanently furnished. Defense Army engineering service of 2005-2008 has done all the planned and urgent measures thus supporting the Defense Army combat readiness, the security of stuff being on duty in emplacements and perfection of fortifying defensive constructions. В 2005-2008 гг. основные усилия инженерной службы Армии Обороны были направлены на обеспечение безопасности личного состава, вовлеченного в боевое дежурство, совершенствованию инженерных и фортификационных строений, выполнению плановых работ и поставленных задач. Поставленные задачи вытекали из необходимости повышения степени огневого поражения противника и сохранения в постоянном обустроенном состоянии оборонительной системы передовой линии. Инженерная служба Армии Обороны в 2005-2008 гг. выполнила плановые и востребованные мероприятия, способствуя боеготовности АО, повышению безопасности личного состава, несущего боевое дежурство и совершенствованию фортификационных сооружений.
Keywords: Պաշտպանության բանակ; Արցախ